Catalytic Cracking of Crude Biodiesel into Biohydrocarbon Using Natural Zeolite Impregnated Nickel Oxide Catalyst - Isalmi Aziz; Edra Aditya Fhilipia Ardine; Nanda Saridewi; Lisa Adhani (Jurnal Kimia Sains dan Aplikasi, 2021)
Crude biodiesel is biodiesel that still contains impurities. A catalytic can improve the quality of biohydrocarbons (biogasoline, biokerosene, and green diesel). The catalyst used is nickel oxide impregnated natural zeolite (NiO/Zeolite). The use of nickel can increase the activity of the catalyst because it has an empty d orbital and a smaller molecular size. This study aims to determine the best catalyst that can exhibit the greatest selectivity toward biohydrocarbons. Natural zeolite was activated and impregnated by varying the concentration of NiO (1, 3, and 5% w/w). The characteristics of the catalyst were determined by the crystallinity (X-Ray Diffraction), surface area (Surface Area Analyzer), and functional group (Fourier Transform Infrared). The catalyst and crude biodiesel were put in an autoclave reactor and operated at a temperature of 375°C and 3 hours. The obtained product was tested with Gas Chromatography-Mass Spectroscopy. The results of the XRD analysis showed the presence of NiO at 2θ 37.23; 43.15; and 62.65°. Nickel oxide on the catalyst was detected at a wavenumber of 671.23 cm‑1. The highest surface area was obtained at a NiO/Zeolite 1% of 49.4 m2/g. 1% NiO/Zeolite catalysts gave the best results on catalytic cracking of crude biodiesel with a reaction conversion of 60.79% and selectivity of 9,73%; 29,64% and 9,18% for biogasoline, biokerosene, and green diesel, respectively.